PERFORMANCE ANALYSIS OF BUSINESS STARTUP WEBSITE USING GT-METRIX WITH WATERFALL SOFTWARE DEVELOPMENT LIFE CYCLE METHOD - Erma Sova; Makmun; Siti Shifa Tasliza (Asosiasi Dosen Muda Indonesia, 2024)
Business ventures began to expand towards technology that initially used conventional sales and payment methods, then developed by young people who saw business opportunities could be simplified in an easy way but had a lot of profit. They utilize computer technology by creating ways to sell through online, namely website media as startup business people. The purpose of the study was to analyze the performance of the